Inflammatory myofibroblastic tumor of the thyroid gland - Zhang, Yiyang; Liu, Jia (Frontiers in Endocrinology, 2023)
Inflammatory myofibroblastic tumor (IMT) is a mesenchymal tumor with low incidence, which is extremely rare in the thyroid. At present, there is a lack of understanding regarding the etiology, pathogenesis, diagnosis and treatment of thyroid IMT. To improve the understanding of the disease, this article reviews the pathogenesis, clinical manifestations, pathology and immunohistochemistry, diagnosis, therapy and prognosis of thyroid IMT.